Using Indicator Chemicals and Online Surrogates to Manage the Chemical Risk of Recycled Water - Linge, Kathryn; Liew, Deborah; Edwards, B.; Blair, P.; Trolio, R.; Cadee, K.; Charrois, Jeffrey (Australian Water Association, 2014)
The Water Corporation of Western Australia’s Groundwater Replenishment Trial (GWRT) has recently tested a new approach for monitoring reverse osmosis (RO) treatment performance using a suite of treatment performance indicator (TPI) chemicals and two online surrogate parameters, conductivity and total organic carbon. It was intended that TPIs would provide a conservative assessment of the removal of unmonitored chemicals with similar physicochemical characteristics. However, while operational and surrogate parameters indicated good RO performance, the calculated removal efficiency of many TPI failed to meet removal targets. External factors, including analytical method uncertainty, low feed concentration, and in some case the potential for chemicals to form within the treatment process, were found to significantly affect calculated removal. It was recommended that RO treatment performance monitoring should focus on surrogate parameters that can be measured online, as they provide immediate feedback that can be linked to variation in plant performance. In contrast, a set of chemical indicators chosen to consider health risks posed by a broad array of chemical classes proved valuable in demonstrating the ongoing safety of the recycled water.